2004
DOI: 10.1002/ejsp.192
|View full text |Cite
|
Sign up to set email alerts
|

Back to caring after being hurt: the role of forgiveness

Abstract: While the topic of forgiveness has only recently started to receive empirical attention, little research has been conducted to examine the notion that forgiveness predicts pro-relationship responses, motivated by a willingness to set aside personal well-being to enhance the well-being of the partner or relationship. The purpose of the present research was to examine whether forgiveness predicts prorelationship responses, and whether it does so above and beyond commitment to the offender. Consistent with hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
127
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(143 citation statements)
references
References 57 publications
8
127
0
8
Order By: Relevance
“…The model further suggests that the link between forgiveness and closeness, and the link between pro-relationship responses and feelings of closeness towards a relationship partner, are bidirectionally related (Karremans & Van Lange, 2004, 2008McCullough et al, 1998). For example, as described in the previous paragraph, it is possible that forgiveness instigates pro-relationship responses, which in turn promote feelings of closeness.…”
Section: Forgiveness In Personal Relationships 233mentioning
confidence: 84%
See 3 more Smart Citations
“…The model further suggests that the link between forgiveness and closeness, and the link between pro-relationship responses and feelings of closeness towards a relationship partner, are bidirectionally related (Karremans & Van Lange, 2004, 2008McCullough et al, 1998). For example, as described in the previous paragraph, it is possible that forgiveness instigates pro-relationship responses, which in turn promote feelings of closeness.…”
Section: Forgiveness In Personal Relationships 233mentioning
confidence: 84%
“…For example, Karremans and Van Lange (2004) demonstrated that participants who were reminded of a past offence that they had largely forgiven (compared to participants who were reminded of a largely unforgiven offence), were subsequently more willing to make a sacrifice for their partner, were more likely to accommodate (i.e., act in a pro-relationship manner) towards a destructive act of the partner (i.e., an act that was unrelated to the past offence), and were more likely to cooperate in a social dilemma task with the partner. For example, in one study participants were reminded of a largely unforgiven offence, or a largely forgiven offence.…”
Section: Interpersonal Effects Of Forgivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Kezdetben a megbocsátásra úgy tekintett a szakirodalom, amely révén az elkövető mentesül tettének következményei alól (FINCHAM, 2009). Így a megbocsátó sértett fél lemond arról a jogáról, hogy a sérelemért elégtételt vegyen, ami ellentmondhat az igazságérzetnek (KARREMANS és VAN LANGE, 2004).…”
unclassified